Traits conferring intermittent drought tolerance across seasons in sesame (Sesamum indicum L.): Traits conferring intermittent drought tolerance across seasons in sesame (Sesamum indicum L.) - P RATNAKUMAR; BRIJ B PANDEY; A SRAVANTHI; E SONIA; M Y DUDHE; Y PRADUMAN; KT RAMYA; H H KUMARASWAMY; K RAMESH; A VISHNUVARDHAN REDDY (Journal of Oilseeds Research, 2020)
Intermittent drought, seasonal temperature variations affect yield of sesame (Sesamum indicum L.) under rainfed conditions. Sesame germplasm were assessed for intermittent drought tolerance across season under field conditions. Seed yield was significantly and positively associated with leaf traits, leaf tissue moisture and CT across seasons. The identified trait specific germplasm will be used further in crop improvement programme.